IO-Based Heart Rate And Blood Oxygen Measurement Monitoring System - Yedi Alsantani; Syarifah Aini; Kms M. Wahyu Hidayat (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
The development of Internet of Things (IoT) technology has driven innovation in the healthcare sector, particularly in real-time and remote monitoring of vital body conditions. This research aims to design and implement an IoT-based heart rate and blood oxygen level (SpO₂) monitoring system using the MAX30100 sensor and the ESP8266 microcontroller. This system was developed to overcome the limitations of conventional monitoring methods that still rely on specialized equipment and direct observation by medical personnel. The MAX30100 sensor is used to measure heart rate and blood oxygen levels based on the principle of pulse oximetry, then the data is processed by the microcontroller and sent to a cloud server via a Wi-Fi connection. The measurement data is displayed in real-time on the Blynk application so that it can be accessed by users anytime and from anywhere. System testing includes heart rate accuracy testing, SpO₂ testing by comparing sensor results to a standard pulse oximeter, IoT connection stability testing, and device durability testing for 6 hours. The test results show that the MAX30100 sensor is capable of producing accurate heart rate and SpO₂ data with small differences compared to standard devices. Furthermore, the IoT connection demonstrated a stability rate of up to 99% without system disruptions. Therefore, this system is considered reliable and suitable for use as a real-time and continuous IoT-based health monitoring solution.